Cultivating Antifragility and Competitiveness of Delima Cakery Sukabumi in the Digital Landscape: Marketing Practices Adapting to the Evolution of the Marketing Mix - Wahdiniwaty, Rahma; Syafei, M. Yani; Firmansyah, Deri; Azhari, Andressa Noviar; Aqsha, Muhammad Farhan (Journal of Community Service and Society Empowerment, 2025)
Disruptive technology increasingly challenges the agility, alignment and ability of SMEs with a quick response in creating products to communicating them to customers through various marketing techniques and management that are increasingly developing in an effort to grow antifragility and business competitiveness. Implementation of P2M by offering training themes and Platform-based marketing practices by adopting the evolution of the 4P marketing mix model in line with the development of digital technology, where "P" for "Place" including becoming a "Platform" that allows marketing communication channels to have a wider reach, with Delima Cakery Sukabumi as the main target partner. The method of implementing activities is operationalized through socialization, product adjustment and innovation, price evaluation and adjustment, determination of the main digital platform according to the business model and product characteristics, and selection of the right promotional program. The results of the implementation of activities are able to improve the ability of Delima Cakery Sukabumi's online marketing practices based on platforms that adopt the evolution of the marketing mix so that they have the potential to grow resilience, antifragility and business competitiveness in the digital era business landscape in the modern era, as measured by the ability to develop and match products, prices, platforms, and promotions.